Photosynthetically Active Radiation using PAR sensor (Biospherical Instruments Inc. QCR-2150) during the Tara Pacific Expedition 2016-2018 - Guillaume Bourdin; Emmanuel Boss; Nils Haëntjens; Fabien Lombard; G Gorsky; Clémentine Moulin; Emilie Boissin; Guillaume Iwankow; Julie Poulain; Sarah Romac; Sylvain Agostini; Bernard Banaigs; et al. (PANGAEA, 2022)
The Tara Pacific expedition (2016-2018) sampled coral ecosystems around 32 islands in the Pacific Ocean, and sampled the surface of oceanic waters at 249 locations, resulting in the collection of nearly 58,000 samples. The expedition was designed to systematically study corals, fish, plankton, and seawater, and included the collection of samples for advanced biogeochemical, molecular, and imaging analysis. Here we provide the continuous dataset originating from PAR sensor (Biospherical Instruments Inc. QCR-2150) acquiring continuously during the full course of the campaign and mounted at the stern of the boat (~7 m altitude).